2017 IFIP/IEEE Symposium on Integrated Network and Service Management (IM) 2017
DOI: 10.23919/inm.2017.7987301
|View full text |Cite
|
Sign up to set email alerts
|

Client-side routing-agnostic gateway selection for heterogeneous Wireless Mesh Networks

Abstract: Abstract-Citizens develop Wireless Mesh Networks (WMN) in many areas as an alternative or their only way for local interconnection and access to the Internet. This access is often achieved through the use of several shared web proxy gateways. These network infrastructures consist of heterogeneous technologies and combine diverse routing protocols. Network-aware stateof-art proxy selection schemes for WMNs do not work in this heterogeneous environment. We developed a client-side gateway selection mechanism that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Such a scenario is typical for ad-hoc networks, IoT networks and community networks. Previous works [3], [4], [9], [13], [14] have demonstrated that in order to receive the best Quality of Service in a large scale dynamic network, client nodes need to have knowledge of the real-time gateway node performances.…”
Section: Experimental Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Such a scenario is typical for ad-hoc networks, IoT networks and community networks. Previous works [3], [4], [9], [13], [14] have demonstrated that in order to receive the best Quality of Service in a large scale dynamic network, client nodes need to have knowledge of the real-time gateway node performances.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The authors of [14] introduce an additional post-processing step where clients adjust measurements received from the cluster head by an estimation of the difference between them and the head. Nonclustering based collaborative algorithms [3], [23] introduce extensive gossiping and measurement overhead to provide accurate sensing. Despite providing accurate measurements, the cost of data exchange between the network nodes are high due to frequent measurements and a wide range of collaboration within network nodes.…”
Section: Related Workmentioning
confidence: 99%
“…However, in a limited resource network, it is often prohibitive to introduce an additional processing overhead in central or in gateway nodes. On the other hand, decentralized gateway selection algorithms require strict cooperation, scheduling and organization between network nodes, often associated to a large amount of communication interchanges between the nodes involved [10].…”
Section: The Proposed Rimo Algorithmmentioning
confidence: 99%
“…To achieve a low monitoring overhead, some works use collaborative probing [8][9][10]. In [8], the monitoring modules collect statistics about network usage.…”
Section: Related Workmentioning
confidence: 99%
“…The providers of these Internet connections can be quite diverse, such as commercial ISP, cooperatives or associations of users sharing costs [15], content or service providers promoting their offer [16], citizens sharing their unused Internet access capacity with neighbors and friends [17], public or private organizations sponsoring Internet access for complimentary interests. However, telecom regulation authorities in many countries limit publicly subsidized Internet access to preserve market competition.…”
Section: The Web Through a Proxy Servicementioning
confidence: 99%